Public Enthusiasm for Islamic Education during the Abbasid Caliphate - Hafizah Hafizah; Yanti Yanti; Latifah Al Ansoriah; Afni Ratna Dewi; Eliza Putri Ardiah; Hairul Amin (Kutubkhanah, 2025)
This study examines the public enthusiasm for Islamic education during the Abbasid Caliphate using a library research approach. It describes the manifestations of public enthusiasm, examines their contributions to the development of educational institutions and activities, and identifies factors, particularly the foundations of the Qur'an and Sunnah, that encouraged the growth of public attention to knowledge. The study focuses on forms of social participation, public support for educational institutions, and the development of a culture of literacy that emerged during that period. The research was conducted through the collection and analysis of relevant historical sources. The results show that educational progress during the Abbasid era was influenced not only by the policies of the caliphs but also by the active involvement of the public in the establishment of educational institutions, literacy activities, and the dissemination of knowledge. Stable political conditions, economic prosperity, multicultural interactions, and the strengthening of Islamic values related to the primacy of knowledge contributed to this dynamic.